End-Permian impactogenic earthquake and tsunami deposits in the intracratonic Parana Basin of Brazil - Tohver, Eric; Schmieder, Martin; Lana, Cris; Mendes, Pedro S. T.; Jourdan, Fred; Warren, Lucas [UNESP]; Riccomini, Claudio (Geological Soc Amer, Inc, 2018)
We investigate the stratigraphic record of the Permian-Triassic intracratonic Parana Basin of South America for evidence of the Araguainha impact event. Soft-sediment deformation features are widespread at distances 50-1000 km from the impact site in the Lopingian (latest Permian) strata of the uppermost Passa Dois Group. Evidence of seismicity includes recumbent folds and slumps, clastic dikes, thixotropic wedges, and autoclastic breccias that resulted from sediment liquefaction. The vertical compaction of clastic dikes indicates their formation prior to sediment lithification, and dike formation is generally confined to stratigraphic intervals with heterolithic beds of varying density and viscosity, i.e., interbedded sandstone and siltstone. These seismogenic features are generally closer to the impact site (<1000 km) versus the distance (>2500 km) to the nearest active plate boundary. Seismites are limited in occurrence to the uppermost 100 m of the paleosurface at the time of impact, and the depth of seismite occurrence decreases with distance from the impact site. Above the seismite interval, the surface is extensively scoured and commonly overlain by a <= 4.5-m-thick debritic event bed. This sedimentary unit, the Porangaba bed, is a matrix-supported, unsorted conglomeratic breccia of variable thickness with an irregular, scoured base and tractional structures, including chaotically oriented to loosely imbricated clasts. Angular to subrounded clasts 10-400 cm in size are composed of altered chert, siltstone, and fine-grained sandstone that were derived from the underlying beds and are arrayed in a fining-upward pattern. In some localities, a second, clast-rich horizon is also observed with similar grading, but it has a smaller average clast size. This debrite bed has been identified in localities across the Parana Basin at distances 50-1200 km from the impact site. The identification of zircon crystals with likely shock metamorphic planar microstructures in multiple samples obtained from this debritic layer links this stratigraphic horizon to the Araguainha impact event, and we interpret this bed as an ejecta-bearing tsunami deposit. The youngest population (n = 12) of unshocked, idiomorphic detrital zircon crystals provides a maximum depositional age of 253.0 +/- 3.0 Ma for this event horizon, contemporaneous, within analytical error, with current geochronologic constraints on the impact event. These findings demonstrate that a catastrophic event around the Permian-Triassic boundary in Brazil created one of the world's most extensive seismite-tsunamite couplets.